CHANGES IN THE AGROCHEMICAL PROPERTIES OF IRRIGATED COLMATED LIGHT SIEROZEMS (Scientific journal of the Fergana State University, 2023)
The paper presents the change in agrochemical properties, salt accumulation, mineralization and the amount of river sediment during the formation of irrigated colmated soils.